Risk factors for error in refractive astigmatism after toric intraocular lens implantation in Chinese patients - Mengyao Zhang; Rui Qin; Yanfeng Liao; Qianqian Ji; Ying Hong (BMC Ophthalmology)
Abstract Background To evaluate the risk factors for postoperative error in refractive astigmatism (ERA) in Chinese patients with cataract and astigmatism undergoing toric intraocular lens (IOL) implantation. Methods Retrospective study. 132 patients who underwent cataract surgery with toric IOL implantation performed by a single surgeon at Peking University Third Hospital Department of Ophthalmology were enrolled. The Barrett Toric Calculator was used to calculate IOL power. Data collected included the patient’s best-corrected visual acuity (BCVA), corneal curvature, central anterior chamber depth (ACD), axial length (AL), incision position, and IOL sphere and cylinder diopters. Corrected visual acuity, ERA, corneal curvature and ACD were collected 1 month after operation. All the participants were divided into two groups according to ERA(whether within 0.5 D or not).Logistic regression was performed to analyze the risk factors for postoperative ERA. Results 112 of the 132 patients (84.8%) had a < 0.5 D postoperative ERA. Logistic regression model showed that older age (OR = 1.102, 95% CI: 1.019–1.192), longer AL (OR = 1.611 95% CI: 1.069–2.429), and higher ΔACD (OR = 4.035, 95% CI: 1.086–15.00) were independent risk factors for postoperative ERA. However, gender, preoperative astigmatism, incision position were not independent risk factors for ERA. Conclusions Factors contributing to ERA after toric IOL implantation include age, AL and ACD change before and after the surgery.